Alkali metal complex-mediated ring-opening polymerization of rac-LA, ε-caprolactone, and δ-valerolactone. (16th May 2019) - Harinath, Adimulam; Bhattacharjee, Jayeeta; Sarkar, Alok; Panda, Tarun K.
Abstract : Catalytic ring opening polymerization (ROP) of rac -lactide, ε-caprolactone, and δ-valerolactone using alkali metal (Li, Na, K) complexes as competent catalysts are reported. Abstract : A series of alkali metal complexes formed by N -(2-fluoro/2-nitro phenyl)- P, P -diphenylphosphinoselenoic amide [(Ph2 P(Se)NH(2-RC6 H4 ))] [R = F (1-H ); NO2 (2-H )] ligands with molecular formulas [M(THF)2 (Ph2 P(Se)N(2-RC6 H4 ))] [M = Li, R = F (3a ), NO2 (3b )] and [M(THF)2 (Ph2 P(Se)N(2-RC6 H4 ))] [M = Na, R = F (4a ), NO2 (4b ); M = K, R = F (5a ), NO2 (5b )] have been synthesized in great yield and fully characterized. The molecular structures of protic-ligands1-H and2-H, and alkali metal complexes3b, 4a, and4b were analyzed using single-crystal X-ray diffraction analysis. Sodium and potassium complexes4a, b and5a, b were proved to be active catalysts for the ring-opening polymerization (ROP) of rac -LA ( rac -LA), ε-caprolactone, and δ-valerolactone at room temperature only. The best isoselectivity of poly(lactide) (PLA) was achieved to a high value of P i = 0.78 using sodium complex4b . One exceedingly dynamic potassium complex (5a, 5b ) even can catalyze the polymerization of 1000 counterparts of rac -LA and yield polylactide with a high molecular weight and narrow polydispersity record (PDI). Experimental outcomes also showed steric hindrance, and electronic impacts have noteworthy consequences for this catalysis in the ROP of rac -LA.